MANAGEMENT OF INNOVATIVE DEVELOPMENT OF AGRICULTURAL ENTERPRISES - Аліна Бричко (Економіка та суспільство, 2022)
The research proposed a solution to the current problem, which consists in substantiating the theoretical foundations and developing practical recommendations for improving the management of innovative development of agricultural enterprises. Achieving the specified goal made it necessary to solve the following tasks, which consisted in the characteristics of innovations in agricultural enterprises. The factors influencing the management of innovative activities of agrarian enterprises are defined. A system of economic levers for the formation of management of innovative development is proposed and directions for increasing the efficiency of management of innovative development of agrarian enterprises.The research proposed a solution to the problem, which consists in justifying the organizational structure of management of the enterprise, which is supplemented by an innovative component of the structural element to ensure the development of the economic entity according to the innovative principle, which will take into account the specialization of the economy, the use of resource-saving technologies, the qualifications of personnel and their material stimulation, commercial calculation and carry out the selection of innovations for use in production and economic activity.